Humanism, antitheodicism, and the critique of meaning in pragmatist philosophy of religion - Pihlström, Sami (American philosophy series, 2023)
"Arguing, humanistically, that we live in a "human world" inescapably colored by meaning, this book shows why the pursuit of meaningfulness is not ethically innocent but must be subjected to critique. Pragmatist critique of meaning both embraces critical humanism and rejects theodicies postulating ultimate meaning in suffering"--